Anti-Inflammatory Effects of Licania macrocarpa Cuatrec Methanol Extract Target Src- and TAK1-Mediated Pathways. (12th September 2019) - Shin, Kon Kuk; Park, Jae Gwang; Hong, Yo Han; Aziz, Nur; Park, Sang Hee; Kim, Sunggyu; Kim, Eunji; Cho, Jae Youl
Abstract : In this study, we investigated the anti-inflammatory effects of Licania macrocarpa Cuatrec methanol extract (Lm-ME) in vitro and in vivo and found pharmacological target proteins of Lm-ME in TLR4-mediated inflammatory signaling. This extract reduced NO production and mRNA expression of inflammatory cytokines such as iNOS, COX-2, IL-6, and IL-1 β . In the NF- κ B- and AP-1-mediated luciferase reporter gene assay, transcription factor activities decreased under cotransfection with MyD88 or TRIF. Phosphorylated protein levels of Src, PI3K, IKK α / β, and I κ B α as well as p50 and p65 in the NF- κ B signal pathway were downregulated, and phosphorylation of TAK1, MEK1/2, MKK4/7, and MKK3/6 as well as ERK, JNK, and p38 was decreased in the AP-1 signal pathway. Through overexpression of HA-Src and HA-TAK1, respectively, Lm-ME inhibited autophosphorylation of overexpressed proteins and thereby activated fewer downstream signaling molecules. Lm-ME also attenuated stomach ulcers in an HCl/EtOH-induced acute gastritis model mice, and COX-2 mRNA expression and phosphorylated TAK1 levels in gastric tissues were diminished. The flavonoids kaempferol and quercetin were identified in the HPLC analysis of Lm-ME; both are actively anti-inflammatory. Therefore, these results suggest that Lm-ME can be used for anti-inflammatory remedy by targeting Src and TAK1.